Shifting the balance of mitochondrial apoptosis: therapeutic perspectives - Fulda, Simone (Frontiers in Oncology, 2012)
Signaling via the intrinsic (mitochondrial) pathway of apoptosis represents one of the critical signal transduction cascades that control the regulation of cell death. This pathway is typically altered in human cancers, thereby providing a suitable target for therapeutic intervention. Members of the Bcl-2 family of proteins as well as cell survival signaling cascades such as the PI3K/Akt/mTOR pathway are involved in the regulation of mitochondria-mediated apoptosis. Therefore, further insights into the molecular mechanisms that form the basis for the control of mitochondria-mediated apoptosis will likely open new perspectives to bypass evasion of apoptosis and treatment resistance in human cancers.